Design and development of dual functional Go-Kart seat - Muhammad Firdaus Mohd Ratmin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project aims to design seat based on ergonomics characteristic and to make the seat has suspension system to isolate the vibration due to surface roughness. This is because the flaw of the product became inconvenient to the driver such as the length of the pedal, length from seat to steering and seat would not suitable their best as they driving and the other problem is the go kart has no suspension.